If \( \frac{6}{\sqrt{3}+3}=a+b \sqrt{3} \), determine the values of \( a \) and \( b \).
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To solve the equation \( \frac{6}{\sqrt{3}+3}=a+b \sqrt{3} \), we can first simplify the left-hand side by multiplying the numerator and the denominator by the conjugate of the denominator, which is \( \sqrt{3} - 3 \). Thus, we have: \[ \frac{6}{\sqrt{3}+3} \cdot \frac{\sqrt{3}-3}{\sqrt{3}-3} = \frac{6(\sqrt{3}-3)}{(\sqrt{3}+3)(\sqrt{3}-3)} \] Calculating the denominator: \[ (\sqrt{3}+3)(\sqrt{3}-3) = 3 - 9 = -6 \] Now, substituting this back into the equation: \[ \frac{6(\sqrt{3}-3)}{-6} = -(\sqrt{3}-3) = -\sqrt{3} + 3 \] This expression can be rewritten as: \[ 3 - \sqrt{3} \] We can now compare this with \( a + b \sqrt{3} \): \[ 3 - \sqrt{3} = a + b\sqrt{3} \] From this, we see that: \[ a = 3 \quad \text{and} \quad b = -1 \] Thus, the values of \( a \) and \( b \) are: \[ \boxed{3} \quad \text{and} \quad \boxed{-1} \]